Numerical Investigation Of Fibre Orientation In Short Glass Fibre Reinforced Injection-Moulded Thermoplastic Composites - Zainudin, Edy Syams (2002)
The aim of this simulation work is to carry out a comparative study of the fibre orientation distribution (FOD) in the short glass fibre reinforced injection moulded thermoplastic (SgFRIMT) composites. The objective of this research is to use a numerical method to investigate the effect of two significant parameters namely, speed of injection and thickness of specimen, on the FOD of the SgFRIMT composites. The numerical simulation is conducted by Moldflow Plastics Insight (MPI) software. MPI software is used to investigate the flow behaviour and to examine the effects of processing conditions on the mouldings. Effects of the thickness of the specimen and injection speed are considered since they have great influence on the mechanical properties of the products. The effect of the injection speed on the FOD is not significant in the thicker plaque. The difference of FOD between the 2 mm and 4 mm plaques has been reported and it was observed that thinner plaque received more aligned fibres at the flow direction due to higher shearing flow generated compared to the thicker one.The fibre orientation is observed for variations from the skin to the core. I n the skin the fibres are highly aligned in the flow direction, whereas in the core the fibres are mainly aligned in the direction transverse to the flow. The more the short fibres are aligned in the moulded parts the better the mechanical behaviour is. Higher injection speeds influence the fibres so as to align along the flow direction but decreases from the skin to the middle/core plane. The overall result of executing the MPI program over the published results gives a full agreement upon the FOD in SgFRIMT composites. The simulated results also agree with other published numerical works. These verify the use of MPI simulation method.